EKSISTENSI LPP TVTRI STASIUN MALUKU SEBAGAI TELEVISI PUBLIK DI ERA DISRUPSI MEDIA - Sukmawati, Lilis; Tuhuteru, Ajuan; Latuconsina, Djabida (Program Studi Ilmu Komunikasi Fakultas Ilmu Sosial dan Politik Universitas Islam Negeri Raden Fatah Palembang, 2024)
Television mass media is one of the mainstream media that has become a reference for access to information by Indonesian people since the New Order to the Reformation Order. However, the presence of digital-based online media (internet) seems to direct all the attention of society, including the need for information. This study aims to analyze the strategy of Maluku station LPP TVRI in maintaining its existence as a public television in the digitalization era. The type of research used is descriptive qualitative with observation methods, in-depth interviews, and documentation. The research results show that there are six things that TVRI Maluku Station strives to maintain its existence as Public Television in the digitalization era (1) TVRI Maluku Station focuses on fostering and compiling content with more weighty broadcast programs, (2) Presenting broadcast programs quality and accepted by the community, (3) Repairing good and sophisticated infrastructure according to the times, (4) Increasing reliable and professional human resources, (5) Building synergy between all parties, namely technical institutions from the ministry of communication and information, the government provincial, district government, and academics who took part in realizing a Victorious TVRI, and (6) TVRI Maluku stations remained consistent in presenting broadcasts that were appropriate following P3SPS (Broadcasting Behavior Guidelines and Broadcast Program Standards) for the public without hunting for ratings.